Scale development: consumer economic nationalistic tendencies (CENTSCALE) - Cheah, Isaac; Phau, Ian (Korean Scholars of Marketing Science, 2012)
Economic nationalism has been identified as a critical component of nationalistic sentiment, influencing cognitions, attitudes, evaluation and purchase intentions. This study develops a scale specifically tailored to measure consumer economic nationalistic tendencies. Scale generation, purification, validation and confirmation are achieved through four studies.